Technology For Overcoming Language Difficulties That Arise In The Development Of Linguistic Competence Of Schoolchildren In English Lessons - Orzikhon MAMAZIYOYEVA (Euro Asian Journal Publishing, 2025)
this article reflects on the difficulties that schoolchildren face in the process of learning a language, ways to eliminate factors that prevent the development of linguistic competence.
Keywords: linguistic; learning; eliminate